2019
DOI: 10.1002/jcb.29446
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The circular RNA‐NRIP1 plays oncogenic roles by targeting microRNA‐505 in the renal carcinoma cell lines

Abstract: We explored the roles and regulatory mechanisms of the circular RNA (circRNA) nuclear receptor-interacting protein 1 (NRIP1; circNRIP1) in ACHN and CAKI-1 cells. ACHN and CAKI-1 cells were transfected with smallinterfering-circNRIP1 (si-circNRIP1) and microRNA-505 (miR-505) inhibitor or the corresponding controls. Cell viability was detected with the Cell Counting Kit-8. The protein expression levels of Bcl-2, Bax, cleaved-caspase-3, matrix metalloproteinase (MMP)-2, MMP-9, adenosine 5′-monophosphate (AMP)acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…In this study, miR-505 blocked malignant episodes of HeLa cells, as demonstrated by higher Bax expression and lower Bcl-2 expression, which were reinforced by the USMB treatment. In line with our findings, the miR-505 inhibitor apparently elevated the cell viability, the colony numbers, and the migration rate, while downregulating the apoptotic rate and Bax expression in renal carcinoma cells [ 33 ]. Also, the overexpression of miR-505 induced the Bax expression in endometrial cancer cells, representing as a possible tumor suppressor [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, miR-505 blocked malignant episodes of HeLa cells, as demonstrated by higher Bax expression and lower Bcl-2 expression, which were reinforced by the USMB treatment. In line with our findings, the miR-505 inhibitor apparently elevated the cell viability, the colony numbers, and the migration rate, while downregulating the apoptotic rate and Bax expression in renal carcinoma cells [ 33 ]. Also, the overexpression of miR-505 induced the Bax expression in endometrial cancer cells, representing as a possible tumor suppressor [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…CircRNAs are reported to closely associate with the progression of a large number of cancers [5]. Aberrant regulation of circRNAs has been noted in gliomas [6], renal cell carcinomas [7] and other human malignancies [8]. With the development of high-throughput sequencing and bioinformatics analysis, increasing numbers of novel circRNAs have been identified to be potential cancer prognostic biomarkers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Researches have shown that circRNA nuclear receptor-interacting protein 1 (circNRIP1, also known as circ_0002711) may act as an oncogene to promote the progression of renal carcinoma and gastric cancer. 15,16 Wang et al used bioinformatics to analyze the differentially expressed circRNAs in OC patients and normal people and found that circNRIP1 was significantly overexpressed in OC patients. 17 However, the role of circNRIP1 in OC progression and whether it participates in the regulation of OC resistance has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%